Military and nature conservation in Peru - Dourojeanni, Marc J. (2020)
It is common not to consider that military governments also adopted important mea- sures for the conservation of natural heritage. However, the reality in Peru and Bra- zil indicates that a significant part of the protected natural areas, as well as laws and other measures to protect biodiversity, were carried out during these democracy inte- rruptions. This note highlights the performance of General Enrique Gallegos in Peru.